The Cultural Symbol of Akkorongtigi in the Wedding Tradition of Makassar Society - Salam, Nur; Lapele, Fitria (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
This research was intended to examine the caltural symbol of Akkorongtigi in Makassar wedding tradition. Moreover, the approach used was a semiotic approach. The data of this research were the documentation of bridal Akkorongtigi activities and verbal utterances which were transcribed into the text. Besides, data collection used were documentation, in-depth interviews, and observations (field recording, recording, and photo shooting). The data analysis stages were carried out through three stages, namely (1) reduction, (2) presentation, and (3) conclusion drawing. Furthermore, the results showed that there were four cultural symbols in Akkorongtigi, namely the symbol of hope, the symbol of religion, the symbol of glory, and the symbol of togetherness. In addition, the representation of the implementation of the Akkorongtigi tradition was supported by two things, they were verbal and nonverbal aspects.Keywords:Symbols, culture, Akkorongtigi, tradition, Makassar